2019
DOI: 10.21763/tjfmpc.610806
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life in Caregivers of the Patients with Hematologic Neoplasms

Abstract: Aim/Background: Malignant diseases impair not only the quality of life of the patient but also the caregivers. The present study aims to investigate the quality of life in caregivers of the patients with hematologic neoplasms and determine the relationship between the subscales of quality of life (QOL) and socio-demographic characteristics of caregivers. Methods: One hundred consecutive caregivers of the patients who were hospitalized at Bone Marrow Transplant Unit and Hematology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Considering research on this topic in Turkey, Gereklioğlu et al [ 21 ] determined that quality of life was affected in 46% of caregivers of PWC. Furthermore, Akpınar and Yurtsever [ 22 ] reported that caregivers who were spouses of PWC had lower quality-of-life scores.…”
Section: Introductionmentioning
confidence: 99%
“…Considering research on this topic in Turkey, Gereklioğlu et al [ 21 ] determined that quality of life was affected in 46% of caregivers of PWC. Furthermore, Akpınar and Yurtsever [ 22 ] reported that caregivers who were spouses of PWC had lower quality-of-life scores.…”
Section: Introductionmentioning
confidence: 99%
“…The lower SF36 scores were obtained from the caregivers included in the study in mental health, vitality, and social functioning subgroups compared to the normal population in a study performed on 96 individuals caring for cancer patients by Grov et al (35). It was determined that pain and mental role were the most affected SF-36 subscales in a study on caregivers of patients with hematological malignancies by Gereklioglu et al (36). Our study is the first to compare Zarit caregiver burden score with SF-36 scores on caregivers of cancer patients in the literature review.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it was determined that the quality of life was affected by 46.6%, and that body pain and mental health were the most affected areas. [ 26 ] In addition, caregivers are more affected because patients frequently apply to the hospital due to developing complications. Therefore, determining the psychosocial and emotional problems of caregivers of patients diagnosed with hematological malignancy will help to develop programs for care services.…”
Section: Introductionmentioning
confidence: 99%